BrachyView: Combining LDR seed positions with transrectal ultrasound imaging in a prostate gel phantom - Alnaghy, S; Cutajar, D L; Bucci, J A; Enari, K; Safavi-Naeini, M; Favoino, M; Tartaglia, M; Carriero, F; Jakubek, J; Pospisil, S; Lerch, M; Rosenfeld, A B; et al. (Physica medica, 2017)
PURPOSE: BrachyView is a novel in-body imaging system which aims to provide LDR brachytherapy seeds position reconstruction within the prostate in real-time. The first prototype is presented in this study: the probe consists of a gamma camera featuring three single cone pinhole collimators embedded in a tungsten tube, above three, high resolution pixelated detectors (Timepix). METHODS: The prostate was imaged with a TRUS system using a sagittal crystal with a 2.5mm slice thickness. Eleven needles containing a total of thirty 0.508U(125)I seeds were implanted under ultrasound guidance. A CT scan was used to localise the seed positions, as well as provide a reference when performing the image co-registration between the BrachyView coordinate system and the TRUS coordinate system. An in-house visualisation software interface was developed to provide a quantitative 3D reconstructed prostate based on the TRUS images and co-registered with the LDR seeds in situ. A rigid body image registration was performed between the BrachyView and TRUS systems, with the BrachyView and CT-derived source locations compared. RESULTS: The reconstructed seed positions determined by the BrachyView probe showed a maximum discrepancy of 1.78mm, with 75% of the seeds reconstructed within 1mm of their nominal location. An accurate co-registration between the BrachyView and TRUS coordinate system was established. CONCLUSIONS: The BrachyView system has shown its ability to reconstruct all implanted LDR seeds within a tissue equivalent prostate gel phantom, providing both anatomical and seed position information in a single interface.
Keywords: Prostatic Neoplasms; prostata; nádory prostaty; Humans; Phantoms, Imaging; Radiotherapy Dosage; Rectum; Ultrasonography; celková dávka radioterapie; lidé; Radiotherapy, Image-Guided; radioterapie řízená obrazem; počítačové zpracování obrazu; Image Processing, Computer-Assisted; Gels; ultrasonografie; Male; Prostate; dávka záření; gely; Radiation Dosage; rektum; mužské pohlaví; fantomy radiodiagnostické; brachyterapie; Brachytherapy